2022
DOI: 10.1590/1984-3143-ar2022-0036
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ficus carica leaf extract on morphological and molecular behavior of mice germ stem cells

Abstract: Infertility is one of the most prevalent health disorders in reproductive-age males and females. Ficus carica (Fc), an herbal plant, has been used traditionally for the treatment of different diseases such as infertility especially in Iranian folk medicine. This study examined the effects of Fc leaf extract on the proliferation of mice spermatogonial stem cells (SSCs). Phenolic, flavonoid content, major polyphenolic compounds and antioxidant activity of the extract was evaluated respectively by Folin-Ciocateu,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…124 In a reproductive toxicity study, Makoolati et al demonstrated that F. Carica had no harmful effects on spermatogonial stem cells and enhanced their viability and proliferation. 125…”
Section: Toxicity Of F Caricamentioning
confidence: 99%
“…124 In a reproductive toxicity study, Makoolati et al demonstrated that F. Carica had no harmful effects on spermatogonial stem cells and enhanced their viability and proliferation. 125…”
Section: Toxicity Of F Caricamentioning
confidence: 99%
“…The control group comprised 70% ethanol (v/v), which was employed for diluting the essential oils. The percentage of total radical scavenging activity was calculated using the following equation (11)(12)(13):…”
Section: The Power Of Radical Scavengingmentioning
confidence: 99%